E-prescription pilot in Poland allows for identification and analysis of primary nonadherence drivers - Przemysław Kardas; Janusz Cieszynski; Marcin Czech; Paweł Lewek (International Journal of Integrated Care, 2019)
Aim: Poland is currently implementing uniform eHealth system on the national level. This system will be using several digital health solutions, such as e-prescription, patient electronic health record, e-referral, etc. One of the first solutions piloted so far was an e-prescription. Along with other major advantages over traditional paper-based prescriptions, e-prescription allows for tracing for primary nonadherence, thanks to comparison of prescriptions issued and dispensed. The aim of this study was to find out major drivers of primary nonadherence among Polish patients, based on e-prescription data. Methods: In this retrospective analysis we used data from the first tranche of e-prescription pilot in Poland, which was completed in September 2018. Medication was considered non-initiated when it was not collected from the pharmacy within one month from the date of prescription. Effect of ACT drug class, and patient characteristics over primary non-adherence was studied with multivariate analysis. Results: Over 24.000 e-prescriptions have been issued in this pilot, for over 5.000 of patients, aged 0-98 year. Most of these prescriptions were for chronic treatments. Multivariate analysis allowed for detailed identification of patients’ groups with the highest risk of primary nonadherence. Several drug classes were find to have increased rate of primary non-adherence Conclusions: E-prescriptions piloted currently in Poland proved to be useful source of information regarding the prevalence of, and the drivers of primary nonadherence. This findings are of great value for public health, and usability in designing national health policy. Therefore, further analyses are planned with the data from the next tranches of e-prescriptions’ pilots, as well as their ultimate nationwide implementation.